The prognostic value of pyeloectasis in infants with urinary syndrome. - Kozachkovsky, A. E.; Vysochina, I. L. (Medicni Perspektivi, 2014)
Aim of the study was of to determine prognostic value of pyeloectasias in the structure of urinary system diseases including the frequency of pyeloectasia and its clinical significance in young children at the stage of hospital treatment at the infectious disease department. The diagnosis of the diseases and malformations of the kidneys and the urinary tract ultrasound study of 192 children at the age of 1 month to – 2,5 years was conducted. Ultrasound study of the urinary system was performed by a standardized technique using ultrasound scanner «SIEMENS SONOLINE G40» (company Siemens, Germany) using a 2.5-5 MHz convex probe, and 7.5-10 MHz linear transducer. Pyeloectasias are the most often sonologic symptom in young age children presenting urinary syndrome (75% of researches). Obtained results of catamnestic follow ups showed that sizes of renal pelvis of more than 10 mm are the risk factors for acute pyelonephritis development.